2017
DOI: 10.1016/j.imbio.2016.09.008
|View full text |Cite
|
Sign up to set email alerts
|

c-Rel is dispensable for the differentiation and functional maturation of M cells in the follicle-associated epithelium

Abstract: M cells reside within the follicle-associated epithelium (FAE) overlying the gut-associated lymphoid tissues. These unique phagocytic epithelial cells enable the mucosal immune system to sample antigens within the lumen of the intestine. The differentiation of M cells from uncommitted precursors in the FAE is dependent on the production of receptor activator of nuclear factor-κB ligand (RANKL) by subepithelial stromal cells. The ligation of a variety of cell surface receptors activates the nuclear factor-κB (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Because NIK acts as a specific component of the non-canonical NF-κB pathway [ 48 ], this result suggested that the RANKL-induced non-canonical NF-κB pathway is essential for M cell differentiation. Recent studies reported that M cell differentiation was dependent on non-canonical RelB pathway, but not canonical c-Rel [ 46 , 47 , 49 ]. However, the canonical NF-κB pathway supports M cell differentiation by enhancing the expression of Relb and Nfkb2 in enteroids stimulated with TNF-α [ 47 ].…”
Section: Differentiation Of M Cellsmentioning
confidence: 99%
“…Because NIK acts as a specific component of the non-canonical NF-κB pathway [ 48 ], this result suggested that the RANKL-induced non-canonical NF-κB pathway is essential for M cell differentiation. Recent studies reported that M cell differentiation was dependent on non-canonical RelB pathway, but not canonical c-Rel [ 46 , 47 , 49 ]. However, the canonical NF-κB pathway supports M cell differentiation by enhancing the expression of Relb and Nfkb2 in enteroids stimulated with TNF-α [ 47 ].…”
Section: Differentiation Of M Cellsmentioning
confidence: 99%
“…Amongst these, the RANKL-mediated activation of the non-canonical NF-κB pathway TF family members NF-κB2 and RelB, and canonical NF-κB pathway TF family members NF-κB1 and RelA, is essential for M cell differentiation ( 18 , 40 ). Activation of c-Rel, in contrast, is dispensable for M cell-differentiation in Peyer’s patches ( 41 ). As anticipated, many of the genes in Cluster 003 were significantly enriched with NF-κB family TF binding site motifs, including RelA and RelB ( Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The effect of organized lymphoid tissues, LTi, and local RANKL production on the adjacent crypt stem cells produces a variety of cell phenotypes in the Follicle Associated Epithelium (FAE) (38); one or more of the TNF related cytokines produced by LTi (as well as FRC and other cells) may account for FAE being uniformly positive for NF-κB activation and relB expression (99101). Yet this global activation of FAE does not explain the sequence of events resulting in crypt cell commitment of a specific subset of enterocytes to M cell production.…”
Section: Organized Lymphoid Tissues and The Life History Of “Constitumentioning
confidence: 99%